If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 7v = 6(6v + 4) Reorder the terms: -5 + 7v = 6(4 + 6v) -5 + 7v = (4 * 6 + 6v * 6) -5 + 7v = (24 + 36v) Solving -5 + 7v = 24 + 36v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-36v' to each side of the equation. -5 + 7v + -36v = 24 + 36v + -36v Combine like terms: 7v + -36v = -29v -5 + -29v = 24 + 36v + -36v Combine like terms: 36v + -36v = 0 -5 + -29v = 24 + 0 -5 + -29v = 24 Add '5' to each side of the equation. -5 + 5 + -29v = 24 + 5 Combine like terms: -5 + 5 = 0 0 + -29v = 24 + 5 -29v = 24 + 5 Combine like terms: 24 + 5 = 29 -29v = 29 Divide each side by '-29'. v = -1 Simplifying v = -1
| 0=2x+3x | | 3(2x-8)-5(15-6x)=9(4x-11) | | 10x+22=-2(x+5) | | 61=-9(v-9)+3(-6+3v) | | 8(k+8)=3k+29 | | 6k+6k=12 | | 5d+54=89 | | 7-7(n+5)=-24-8n | | -7n-5=-5(n-1) | | 9r-5r-6r= | | -3x-1x=-12 | | 3x-12=2(5x-10) | | 14+x=6-x | | -6v-30=-6(1+2v) | | -6-8=n | | x+(x+120)+2x=660 | | 2y=2(y-3) | | 13x+6=(x+6) | | 11(3x-2)+12=-10(1+10x) | | x-4(1+2x)=-8x-10 | | 5=-1+2k+4k | | 8-14=n | | 11x+6=2x+24 | | 6y-10=6y+10 | | 7z+7-3z=10+3z+7 | | -24+8n=8(n-6)-6n | | 9-10n=-81 | | 4(4-w)=2(-5+4y) | | -5-8a=8-7(a+2) | | 40=8(-1-7x)+4(-3x-5) | | 3x-8=6x-4 | | 7(m-4)+8m=14+8m |